(untitled) (Iter, 2022)
This article develops some aspects o f the notion o f evidence or p ro o f in the so-called biomedical Sciences, emphasizing that they constitute communities o f methods rather than o f truths. The notion o f truth in an absolute sense is absent from the scientific discourse and is replaced by the vague term “evidence ” in its least concrete connotations. This means a displacement from goals or ends o f knowledge to the means which permit its construction. Some implications o f this scenario indícate the need o f a dialogical perspective in the social construction o f knowledge aasociated with the professions related to health and healthcare.